PENGARUH KINERJA ACCOUNT REPRESENTATIVE, KUALITAS PELAYANAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Hana Muyesca Irvani; Haryono (Publika Citra Media, 2026)
This study aims to analyze the influence of Account Representative performance, service quality, and tax sanctions on the compliance of individual taxpayers. Taxpayer compliance is one of the key factors in optimizing state revenue from the taxation sector. The method used in this research is a quantitative approach with a survey technique, utilizing a Google Form questionnaire distributed to 100 individual taxpayers registered at the Tax Service Office. The data collected are primary data and were statistically analyzed to determine the effect of each independent variable on the dependent variable. The results show that simultaneously, the performance of Account Representatives, service quality, and tax sanctions have a significant effect on individual taxpayer compliance. Partially, each of the variables also has a positive and significant impact. These findings indicate the importance of improving the competence of tax officers, enhancing the service system, and enforcing firm and fair sanctions to increase tax compliance.